In Search of Elegance in the Theory and Practice of Computation Essays Dedicated to Peter Buneman - Tannen, Val.; Wong, Limsoon; Libkin, Leonid; Fan, Wenfei; Tan, Wang-Chiew.; Fourman, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This Festschrift volume, published in honour of Peter Buneman, contains contributions written by some of his colleagues, former students, and friends. In celebration of his distinguished career a colloquium was held in Edinburgh, Scotland, 27-29 October, 2013. The articles presented herein belong to some of the many areas of Peter's research interests.
Models for Data-Centric Workflows -- Relational Databases and Bell$1 (Bs Theorem -- High-Level Rules for Integration and Analysis of Data: New Challenges -- A New Framework for Designing Schema Mappings -- User Trust and Judgments in a Curated Database with Explicit Provenance -- An Abstract, Reusable, and Extensible Programming Language Design Architecture -- A Discussion on Pricing Relational Data -- Tractable Reasoning in Description Logics with Functionality Constraints -- Toward a Theory of Self-explaining Computation -- To Show or Not to Show in Workflow Provenance -- Provenance-Directed Chase and Backchase -- Data Quality Problems beyond Consistency and Deduplication -- Hitting Buneman Circles -- Looking at the World Thru Colored Glasses -- Static Analysis and Query Answering for Incomplete Data Trees with Constraints -- Using SQL for Efficient Generation and Querying of Provenance Information -- Bounds and Algorithms for Joins via Fractional Edge Covers -- Incremental Data Fusion Based on Provenance Information -- Provenance for Linked Data -- First-Order Provenance Games -- Querying an Integrated Complex-Object Dataflow Database -- Types, Functional Programming and Atomic Transactions in Hardware Design -- Record Polymorphism: Its Development and Applications -- A Calculus of Chemical Systems -- Schemaless Semistructured Data Revisited - Reinventing Peter Buneman$1 (Bs Deterministic Semistructured Data Model -- Provenance Propagation in Complex Queries -- Well-Defined NRC Queries Can Be Typed -- Nine Years with Peter Buneman -- Modal Logic for Preference Based on Reasons -- The Dichotomous Intensional Expressive Power of the Nested Relational Calculus with Powerset -- Provenance in a Modifiable Data Set.s
Keywords: Computer science; Logic design; Database management; Computer Science; Database Management; Programming Languages, Compilers, Interpreters; Logics and Meanings of Programs